Study of Patient Billing Calculation System at PKU Muhammadiyah Mamajang Hospital Makassar - Irviani Anwar Ibrahim1; A. Syamsiah Adha (Homes Journal: Hospital Management Studies Journal, 2025)
Backround: A Sharia hospital is a healthcare institution that applies Islamic principles in its management and services. Objective: This study aims to analyze the implementation of Sharia principles in healthcare services at PKU Muhammadiyah Mamajang Hospital. Methods: Using a qualitative approach, this research was conducted through in-depth interviews and observations of Sharia service practices. Result: The findings indicate that the employment contract for healthcare workers follows the wakalah contract, while the contract with patients is carried out through the informed consent mechanism. The hospital has implemented a clinical pathway and Clinical Practice Guidelines (PPK), yet challenges remain in applying Sharia principles, such as inconsistencies in patient examinations based on gender and limitations in supporting facilities, such as Sharia-compliant breastfeeding attire. Sharia supervision is still conducted internally without a dedicated Sharia Supervisory Board (DPS). Conclusion: Therefore, strengthening internal policies, enhancing healthcare worker training, and optimizing Sharia-based facilities are necessary to improve the quality and consistency of services in accordance with Sharia principles.